2016
DOI: 10.1007/s11262-016-1365-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of novel ferret coronaviruses and evidence of recombination among ferret coronaviruses

Abstract: In an epidemiological study of ferret coronaviruses (FRCoVs), novel FRCoV strains (Saitama-1 and Aichi-1) were detected by reverse transcription-polymerase chain reaction (RT-PCR) and nucleotide sequence analysis of partial RNA-dependent RNA polymerase (RdRp) genes. Phylogenetic analysis indicated that these strains belonged to different clusters from other FRCoV strains. Next, the nucleotide sequence of the 3'-terminal region of Saitama-1 (8271 bases) strain was determined and compared with those of the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Thus far, most of the recombination events of coronaviruses have been reported between species of the same group (Herrewegh et al, 1998;Keck et al, 1988), such as among the batassociated CoVs (Corman et al, 2014) and 229E-related CoVs (Corman et al, 2015), and the major recombination breakpoint has mainly been within the S gene. Genetic recombinant among alphacoronavirus 1 species frequently occurred, such as ferret coronaviruses (Lamers et al, 2016;Minami et al, 2016). However, few researches about genetic recombination of Betacoronavirus 1 species have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, most of the recombination events of coronaviruses have been reported between species of the same group (Herrewegh et al, 1998;Keck et al, 1988), such as among the batassociated CoVs (Corman et al, 2014) and 229E-related CoVs (Corman et al, 2015), and the major recombination breakpoint has mainly been within the S gene. Genetic recombinant among alphacoronavirus 1 species frequently occurred, such as ferret coronaviruses (Lamers et al, 2016;Minami et al, 2016). However, few researches about genetic recombination of Betacoronavirus 1 species have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination in coronaviruses plays an important role in virus evolution and can result in the emergence of new pathotypes (Menachery, Graham, & Baric, ; Wang et al, ) as well as changing the host ranges and ecological niches (Bakkers et al, ). Thus far, recombination regions in coronaviruses have been extensively reported for the S gene (Kin et al, ; Lau et al, ; Minami et al, ), a finding also applicable to BCoV (Martínez et al, ). Recombination events in M (Herrewegh, Smeenk, Horzinek, Rottier, & Groot, ), N (Kin et al, ), RP3 (Lau et al, ) and the ORF1 gene (Chen et al, ; Kin et al, ) have also been reported.…”
Section: Introductionmentioning
confidence: 93%
“…Recombination in coronaviruses plays an important role in virus evolution and can result in the emergence of new pathotypes [ 7 ]. Thus far, recombination regions in coronaviruses have been extensively reported for the S gene [ 8 ]. BCoV is transmitted via the fecal-oral or respiratory route [ 9 ].…”
Section: Introductionmentioning
confidence: 99%